Fatores Determinantes da Posição Trófica em Consumidores Aquáticos, Fatores Macroecológicos e Evolutivos - Guilherme Dalponti (2021)
The maintenance of a positive energetic budget is critical for a consumer’s survival and reproductive success, strategies that maximize the energy acquirement and minimize expenditure fundamentally shape biological interactions, organisms that present the most efficient strategies for the assimilation of nutrients and energy can allocate more resources on reproduction and can propagate their characteristics. Species may develop different adaptations in order to maximize the relationship between energy assimilation/expenditure depending on morphological, physiological or environmental constraints. On this thesis I focus on the body size – trophic position relationship in marine consumers given that the relationship between these two traits can be very important on species energy budget influencing their means to acquire resources and on their metabolic rates and is also influenced by climatic and environmental conditions. On the first chapter I used a dataset published by Jennings & Cogan (2015) to investigate the body size – trophic position relationship in fish and squid species exploring intra and interspecific variations in order to understand the mechanisms that lead to the pattern of a positive relationship between trophic position amplitude and body size in ectothermic aquatic consumers, I found out an overall positive relationship between body size and trophic position and specific responses on the relationships between body size and trophic position amplitude within species. On the remainder of the thesis I focus on the effect of climatic and environmental variables on the body size trophic position, comparing temperate, tropical, marine and freshwater bony fish species, ectothermic species have their metabolic rates regulated by the environmental temperature, meaning that ectothermic species inhabiting warm regions have different, usually higher metabolic rates than species inhabiting colder regions, also environment type may influence on the availability of resource, for example freshwater environments are usually smaller and very influenced by alochtonous input of organic matter, leading to differences on the 6 characteristics related to feeding strategies and energetic expenditure, for example trophic position and body size, as well as on the relationship between these characteristics. The last two chapters focus on the effects of climate and environment on the evolutionary relationships between body size and trophic position in bony fish. In the second chapter I investigated the evolutionary rates and rates of correlated evolution of body size and trophic position using a global dataset fitted to the latest published evolutionary tree on bony fish to date, I found out that the body size – trophic position relationship is more evident on the tropical climate and that this pattern is likely caused by different evolutionary correlation between body size and trophic position on different climates. In the last chapter I am worked with species diversification models taking into account climatic region as well as species trophic guilds to identify which factors lead to more rapid or slow species diversification, finding out that the prevalence of herbivory in the tropics may be due to higher diversification of low trophic position guilds in these regions.